Modules of continuity and analytic functions - Trohimchuk, Yu. Yu (Ukrains’kyi Matematychnyi Zhurnal, 2010)
For a function analytic in a compact domain and continuous in its closure, it is shown that the modules of continuity on the boundary of the domain and in its closure coincide.